Mental health and quality of life in children and adolescents during the COVID-19 pandemic: a systematic review of longitudinal studies - Orban, Ester; Li, Lydia Yao; Gilbert, Martha; Napp, Ann-Kathrin; Kaman, Anne; Topf, Sabine; Boecker, Maren; Devine, Janine; Reiß, Franziska; Wendel, Flora; Jung-Sievers, Caroline; Ernst, Vanessa Sophie; et al. (Frontiers in Public Health, 2024)
The COVID-19 pandemic has significantly impacted the mental health of children and families, i.e. due to measures like social distancing and remote schooling. While previous research has shown negative effects on mental health and health-related quality of life (HRQoL), most studies have focused on pre-post comparisons in the early pandemic stages. This systematic review aims to examine longitudinal studies to understand the long-term impacts of the pandemic on children and adolescents. This systematic review adhered to the PRISMA guidelines and was preregistered in the international prospective register of systematic reviews (Record ID:CRD42022336930). We systematically searched Pub-Med/MEDLINE, Web of Science, PsycINFO, PSYNDEX, and the WHO-COVID-19 database and included studies published up to 30 August 2022. Based on predefined eligibility criteria, longitudinal and prospective studies assessing the mental health or HRQoL of children or adolescents in the general population over a longer time span (at two or more measurement points) during the COVID-19 pandemic were included. The methodological quality of the included studies was assessed using an adapted version of the Effective Public Health Practice Project checklist. Narrative data synthesis was used to summarize findings. A total of 5,099 results were obtained from literature searches, with 4,935 excluded during title/abstract screening. After reviewing 163 full-text articles, 24 publications were included in the review. Sample sizes ranged between n=86 and n=34,038. The length of the investigated time periods and the number of assessment points, as well as outcomes, varied. The majority of studies were of moderate methodological quality. Mental health outcomes were more frequently studied compared to measures of HRQoL. The findings from these studies mostly suggest that children and adolescents experienced heightened mental health problems, specifically internalizing symptoms like anxiety and depression. Further, there was a decline in their overall HRQoL throughout the COVID-19 pandemic that did not necessarily subside when lockdowns ended. It is crucial to continue monitoring the mental health of young people following the pandemic to identify groups at risks. This should ideally be conducted by large systematic studies, using validated instruments, and encompassing representative samples to obtain reliable and comprehensive insights aimed at improving youth mental health care.